PEMBERDAYAAN MASYARAKAT DALAM KESIAPSIAGAAN BENCANA ERUPSI GUNUNG MARAPI DAN BANJIR BANDANG DI NAGARI BUKIK BATABUAH KABUPATEN AGAM - Trisfa Augia; Sosmiarti Sosmiarti; Hendery Dahlan; Adelia Fauziah; Dwinda Yoanda; Felina Azzahra; Gita Felisha Astra (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Bukik Batabuah is one of the villages affected by the flash flood and the eruption of Mount Marapi some time ago. The impact of the disaster on the community is not only the loss of property and housing, but also the loss of life. Based on this, it is necessary to make efforts to increase community preparedness for disasters. The purpose of this activity is to increase the knowledge, abilities of the community and nagari apparatus about disaster preparedness and reforestation to restore affected land and prepare an early warning system through the Community Partnership Program to Help Nagari Build. The method of activity is training for disaster preparedness and first aid for 20 members of the Disaster Preparedness Group and nagari apparatus for one day. Furthermore, socialization and simulation of disasters and the importance of implementing Clean and Healthy Living Behaviors for 83 elementary school students for five days. Reforestation and remediation efforts on affected land are carried out through the assistance of 704 tree seedlings. Assistance of 10 kentongan was given for early warning with local wisdom. The results of the activity showed an improvement in the ability of trainees and elementary school students in disaster preparedness as well as a commitment to continue reforestation and remediation as well as the use of kentongan for disaster early warning. Based on the results of the activity, it can be concluded that the people of Nagari already understand and have the ability to deal with emergencies during disasters as an effort to mitigate disasters. It is hoped that this program can be carried out regularly in Nagari Bukik Batabuah and become a model for other disaster-prone areas in West Sumatra. In addition, synergy between educational institutions, local governments, and communities in building resilience to disasters is needed to avoid adverse impacts due to disasters.